Analyzing 16S rRNA sequences from Vietnamese pathogenic Leptospira strains and in-silico prediction of potential antigenic epitopes on LipL21, LipL32 outer membrane lipoproteins - Bich Thuy, Vo Thi; Tuan Hung, Nguyen; Ngoc Minh, Nghiem (Vietnam Journal of Biotechnology, 2020)
Leptospirosis, a zoonosis caused by Leptospira, is recognized as an emergent infectious disease. In currently, the lack of adequate diagnostic tools, vaccines are an attractive intervention strategy. In this experiment, a 550 bp fragment of large ribosomal RNA gene (16S rRNA) was sequenced and constructed phylogenetic tree from a panel of six Vietnamese pathogenic strains of Leptospira spirochetes (e.g., Pomona, Canicola, Mitis, Ictero haemohagiae, Bataviae, and Grippotyphosa). The results showed a close relationship of L.Pomona_VN and L.Hardjo (bootstrap: 99%). L.Canicola_VN and L.Ictero haemohagiae_VN appeared to be weak related to the classic L.Canicola, L. Grippotyphosa, these assemblage have a bootstrap support of 62%. The other strains (L.Mitis_VN and L.Grippotyphosa_VN) were appeared monophyletic, while their sister group (L.Bataviae_VN) relationship found only weak support (bootstrap: 62%). We also selected six genes [e.g. the immunoglobulin like proteins A and B (LigA and LigB genes), outer membrane protein (OmpL1 gene), and lipopolysaccharide (LipL32, LipL41, and LipL21 genes)] and checked gene expression in these Leptospira strains by polymerase chain reaction (PCR) method. There were three genes (e.g., LipL32, LipL21, and LigA genes) expressed in all strains, OmpL1 gene occured in 4 strains (L.Bataviae_VN, L.Canicola_VN, L.Grippotyphosa_VN and L.Mitis_VN), whereas LipL41 and LigB genes did not appear in any Leptospira strains. A multi-antigenic epitope potential of two gene (Lip L21 and Lip L32) was predicted by bioinformatic tools for designing a recombinant vaccine against leptospirosis. There were 3 multi-epitope regions (1 region and 95 antigenic epitope for B and T cells of LipL21 peptide; 2 regions and 124 antigenic epitope for both B and T cells of LipL32 peptide). It should be more of the deeply molecular biology studies to confirm the level agglutinating, antigen cleavage, peptide specificity matrices as well as neutralizing antibodies in the immune responses of DNA vaccine of these genes.